Third Language Acquisition and Universal Grammar. - Leung, Yan-kit Ingrid (Channel View Publications, 2009)
Third Language Acquisition and Universal Grammar contains nine chapters on adult third language (L3) or multilingual acquisition from the Universal Grammar (UG) perspective. A variety of languages other than English are involved in the studies reported in the papers, including Cantonese Chinese, French, German, Italian, Japanese, Kazakh, Mandarin Chinese, Norwegian, Russian, Spanish, Tagalog, and Thai, with acquisition cases taking place in a number of different geographical locations, such as Canada, Germany, Hong Kong, Norway, Taiwan, Thailand, the UK and the USA. This volume will appeal to.